2021
DOI: 10.1111/and.14144
|View full text |Cite
|
Sign up to set email alerts
|

Secretions released from mesenchymal stem cells improve spermatogenesis restoration of cytotoxic treatment with busulfan in azoospermia mice

Abstract: This study aimed at the efficacy of sequential treatment of bone marrow‐derived mesenchymal stem cell secretion for busulfan‐treated azoospermia in mice. The conditioned media (CM) was obtained from bone marrow mesenchymal stem cells (MSCs) or 293 cells. Chemically induced azoospermia mice received 200 μl MSC‐CM or 293‐CM twice a week intravenously for three consecutive weeks. The histological assessment of spermatogenic recovery quantifying the expression of meiosis‐associated genes, and Sertoli cell barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…In the murine model of busulfan-induced spermatogenesis injury, it was shown that the systemic administration of MSC secretome leads to the increased mRNA expression of N-cadherin and ICAM1, which are involved in the barrier function of Sertoli cells. Moreover, the MSC secretome-treated group in the study showed the best results in experimental wound healing by the TM4 Sertoli cell line in a scratch assay conducted in the early stages of observation [88]. This result was consistent with the hypothesis that MSC secretome could attract Sertoli cells to the injured niche from specific transient zones of the adult testes.…”
Section: Spermatogonial Stem Cell Niche As a Promising Target To Asse...supporting
confidence: 85%
“…In the murine model of busulfan-induced spermatogenesis injury, it was shown that the systemic administration of MSC secretome leads to the increased mRNA expression of N-cadherin and ICAM1, which are involved in the barrier function of Sertoli cells. Moreover, the MSC secretome-treated group in the study showed the best results in experimental wound healing by the TM4 Sertoli cell line in a scratch assay conducted in the early stages of observation [88]. This result was consistent with the hypothesis that MSC secretome could attract Sertoli cells to the injured niche from specific transient zones of the adult testes.…”
Section: Spermatogonial Stem Cell Niche As a Promising Target To Asse...supporting
confidence: 85%
“…SCs can also reduce mitochondrial apoptosis to restore fertility [236]. Cai et al reported that BM-MSCs restore fertility in cases of busulfaninduced azoospermia by releasing proteins, including angiogenic factors, antiapoptotic factors, chemokines, cytokines, and immunoregulators [240]. Furthermore, normal spermatogenesis was restored in the individuals with testicular toxicity using a conditioned medium derived from BM-MSCs [241] and exosomes derived from urine-derived SCs [242].…”
Section: Gonadotoxicitymentioning
confidence: 99%